RETRACTED: Economic assessment of the effects of the introduction of digital platforms for the integration of participants in mixed (multimodal) freight transport (based on rail transport) - Gulyi Ilia; Kornienko Elizaveta (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001